Investigation of High-Temperature Tensile Properties and Fracture Mechanisms of GH3536 Alloy Fabricated by Selective Laser Melting - Biao Zhou; Shuai Huang; Tianyuan Wang; Cheng Wang; Bingqing Chen (Metals)
This work revealed the mechanism of microstructure evolution on tensile properties in selective laser melted (SLM) GH3536 superalloys in the range of room temperature to 1000 °C. The results showed that SLM-GH3536 alloy exhibited isotropic tensile properties along X, Z, and 45° directions. The carbide at the grain boundary changed from banded to granular, resulting in a significant decrease in tensile strength at elevated temperatures, and the fracture mode transitioned from a mixed fracture to transgranular fracture.